Root system architecture of paddy in potassium acquisition / Muhammad Nur Amin Mohd Jailani - Mohd Jailani, Muhammad Nur Amin (Faculty of Plantation and Agrotechnology, 2019)
Potassium (K) is an essential nutrient for plant growth. However, there are only little information about the effects of potassium on plant root architecture available. The research was conducted under in-vitro tissue culture technique to observe the influence or effect of different K levels on paddy root system architecture (RSA) and the differences in length of seminal root (SR) and number of lateral (LR) and crown roots (CR) in paddy. Four treatments with different concentrations of potassium (K) fertilizer (Muriate of Potash) with 5 replications were used. The four treatments are categorized into control, 0, 0.01g and 0.1g levels of fertilizer. After fourteen days of germination period, the image of RSA was taken to compare the overall architecture. The seminal root length was measured, and the number of lateral and crown root was recorded to analyse the differences between different amounts of Potassium. The outcome showed that the number of crown root decreases as the amount of potassium increase. Although the number of lateral root shows no huge significant between different amounts of Potassium, the highest number of LR were recorded at the 0.1g treatment. The highest measurement of SR was observed in 0g of K. However, the treatment with 0.1g of K showed only slight different in length of SR in 0.1g treatment.